Assessing and mapping water-energy-food nexus smart innovations and practices in Vhembe District Municipality, Limpopo Province, South Africa - Musetsho, Khangwelo D.; Mwendera, Emmanuel; Madzivhandila, Tshilidzi; Makungo, Rachel; Volenzo, Tom E.; Mamphweli, Ntshengedzeni S.; Nephawe, Khathutshelo A. (Frontiers in Water, 2024)
Water, energy and food and their interactions (commonly referred to as the WEF nexus) are critical pillars to resolving the intractable global challenges such as poverty, hunger, malnutrition, poor sanitation, climate, and health crises. The nexus approach, practices and innovations at the household level are critical determinants of whether resource use efficiency, co-benefits, basic rights to water and food, and sustainability governance are attained. In particular, smart WEF innovations can contribute to the current generations' economic, social, and environmental needs without compromising the needs of the future generation. The study aimed to identify smart innovations, practices, and factors influencing their adoption to inform policy and decision-making processes. The study intends to support scaling up the adoption of innovations and practices that enhance sustainability and resource security in support of the sustainable development goals (SDGs). Semi-structured interviews and key informant interviews (KII) supplemented with observational checklists were used to identify the WEF nexus smart technologies, innovations, and practices in Vhembe District Municipality, Limpopo Province, South Africa. Data was collected from a sample size of 128 households in the study area.Our findings revealed synergistic smart innovation practices across WEF resource use and management practices. Though indigenous knowledge (IK) practices were widely evident in the study area, nonexistent WEF smart knowledge support systems existed in the study area. Indigenous knowledge practices were the most elicited innovation by 99.2% of households, suggesting it is critical to advancing WEF smart innovations and practices and needs to be integrated into any policy and governance interventions. A proportion of households recycle water (27%), whilst 53% use untreated water. Furthermore, the knowledge systems on smart WEF Innovations were fragmented despite their potential to synergise sustainability objectives. Exploring innovation platforms (IPs) as vehicles for dissemination, innovation, and extension and advisory service delivery, as well as validation of IKS, has the potential to contribute to the diffusion, uptake and scaling of existing innovation and practices with significant spill-over effects on WEF resource security and sustainability outcomes both at local and extra local scales.